Urgensi Kantor Komunikasi Presiden dalam Sistem Pemerintahan - Allan Fatchan Gani Wardhana; Firdha Susanto; Safira Ika Maharani (Fakultas Hukum Universitas Islam Indonesia, 2025)
The position of the Presidential Communication Office as a Non-structural Institution has raised both pros and cons debates that have led to a review of the urgency of the existence of this new institution. This study examines two things, first, the position, duties, functions, and institutional structure of the Presidential Communication Office and second, the urgency of the Presidential Communication Office in the Government System. The results of this study are, first, the Presidential Communication Office is a non-structural institution under and responsible to the President. Its position, functions, and duties are intended to provide support to the President in implementing communication and information on strategic policies and priority programs of the President. Second, the existence of the Presidential Communication Office needs to be reviewed in more depth, especially regarding the possibility of overlapping with the Ministry of Communication and Digital. In addition, the institutional structure of the Presidential Communication Office has the potential to conflict with the spirit of bureaucratic reform, if not followed by the arrangement of government institutions that have the same authority.